Pemanfaatan Sistem Informasi Manajemen Daerah Pada Kinerja Pengelola Keuangan dan Kepuasan Pengguna Sebagai Variabel Intervening - Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
This study aims the local management system (SIMBA) on financial management performance with user satisfaction as an intervening variable This research was conducted on OPD in Bengkulu Province. This type of research is quantitative. The data used are primary data obtained from questionnaires. Sample selection using the Census method. Data were analyzed using Structural Equation Modeling with Partial Least Squares (PLS) and using SmartPLS 5 software. The results showed that the use of information systems and financial management satisfaction had a positive effect on financial management performance in OPD in Bengkulu Province or 72.5%.